1974
DOI: 10.1002/art.1780170307
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rabbit articular cartilage organ model II. 35S incorporation in various oxygen tensions

Abstract: Adult rabbit articular cartilage slice and plug explants were cultured in MEM/NCTC 109/fetal calf serum at 37°C in various oxygen tensions. In both the slice and plug explants, 85S04 incorporation exhibited a broad tolerance to oxygen tensions varying from 5 (38 mm. Hg) to 60 (456 mm Hg) per cent. Significantly (P 0.01) less 35S04 was incorporated in 1 (7.6 mm Hg) and 90% (684 mm Hg) oxygen than in 21 % (160 mm Hg) oxygen. No histologic or autoradiographic differences, and only slight histochemical differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…If low PI,O2 values occur in the deeper parts of the joint under physiological conditions, this could have important consequences if the joint sustains injury or becomes diseased. In a rabbit in vitro articular cartilage model it was found that low PO2 was detrimental to cartilage glycosaminoglyean metabolism resulting in inhibition both of cellular proliferation and synthesis of extracellular ground substance (Brighton, Lane & Koh, 1974;Lane, Brighton & Menkowitz, 1977). If joint injury or disease caused still further reduction in P, 02' this could contribute to, or perhaps initiate, processes such as cartilage destruction, angiogenesis and fibroblast proliferation which are known to occur in conditions such as rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…If low PI,O2 values occur in the deeper parts of the joint under physiological conditions, this could have important consequences if the joint sustains injury or becomes diseased. In a rabbit in vitro articular cartilage model it was found that low PO2 was detrimental to cartilage glycosaminoglyean metabolism resulting in inhibition both of cellular proliferation and synthesis of extracellular ground substance (Brighton, Lane & Koh, 1974;Lane, Brighton & Menkowitz, 1977). If joint injury or disease caused still further reduction in P, 02' this could contribute to, or perhaps initiate, processes such as cartilage destruction, angiogenesis and fibroblast proliferation which are known to occur in conditions such as rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while they tolerate very low oxygen tensions more successfully than do fibroblasts, chondrocytes do not thrive under such conditions. Synthetic activity is also reduced by very high oxygen tensions (Marcus, 1973;Brighton et al, 1974). Since cartilage cellularity varies over a wide range the glycolytic and respiratory rates (Table 1) of the whole tissue tend to reflect cell density.…”
Section: Metabolismmentioning
confidence: 99%
“…Possibly as a result of their low ambient O 2 , chondrocyte metabolism is almost entirely glycolytic. Nevertheless, removal of O 2 has marked effects, depressing both metabolism (reducing adenosine triphosphate (ATP) levels and lactate production-the negative Pasteur effect) almost immediately [17] and inhibiting matrix synthesis [2,7,12,40].…”
Section: Introductionmentioning
confidence: 99%